Pelatihan Hidroponik Berbasis Deep Flow Technique bagi Kader Posyandu untuk Penguatan Ketahanan Pangan Rumah Tangga di Desa Babulu Darat - Hamdani, Dadan; Sari, Syaharani Puspita; Anugro, Fawwaz Apto; Ekaviyanti, Ekaviyanti; Amanda, Nia; Khoiriyah, Khoiriyah; Simanjuntak, Dani Josafat; Akbarri, Destri Amelia; Andriana , Riska Dwi; Ar Rasyid, Muhammad Dhia; Hafidz, Muhammad Fauzil; Munir, Rahmawati (Jurnal IPTEK Bagi Masyarakat, 2025)
The hydroponic training activity in Babulu Darat Village was carried out to support household food security through the empowerment of Posyandu cadres. This program aimed to improve participants’ knowledge and practical skills in applying the Deep Flow Technique (DFT) hydroponic system that can be implemented in home gardens. Using a participatory approach, the training included presentations, interactive discussions, and hands-on practice in assembling installations and cultivating leafy vegetables. Evaluation results based on pre-test and post-test assessments of 25 participants showed a significant improvement in knowledge, with the average score increasing from 56% to 81% after the training. This demonstrates the effectiveness of the DFT-based hydroponic training in enhancing both understanding and application skills. Participants expressed strong enthusiasm and readiness to continue developing hydroponics independently. The program contributed directly to strengthening household food security and supporting the achievement of Sustainable Development Goal (SDG) 2 is Zero Hunger through the promotion of community-based sustainable food self-reliance.